The post-activation performance enhancement effect of different plyometric training modalities on short-distance sprinting: An acute randomized crossover study - Wenhao Qu; Wuwen Peng; Yueming Li; Lin Xie; Jian Sun; Duanying Li (PLoS ONE, 2026)
Objective This study aimed to investigate the effects of different plyometric training modalities [vertical jump plyometric training (VJ-PT), horizontal jump plyometric training (HJ-PT), and combined jump plyometric training (CJ-PT)] on post-activation performance enhancement (PAPE) in short-distance sprint performance. Methods A randomized crossover design was employed, with 12 participants (sex: male; age:19.6 ± 0.9; BMI:24.9 ± 3.85). recruited for this study. Participants underwent three training interventions: VJ-PT, HJ-PT, and CJ-PT. Each training protocol consisted of 2 sets × 6 repetitions of one of the jump training modalities. The Smart Speed system was used to assess 5-meter sprint performance pre-intervention and at 4, 8, 12, and 16 minutes post-training. Repeated-measures ANOVA and Pearson correlation analyses were conducted using SPSS 26.0 and JASP 18.3. Results No significant effects were observed for time (F = 1.43, p = 0.23), intervention (F = 0.32, p = 0.72), or interaction (F = 1.03, p = 0.41). However, VJ-PT demonstrated moderate effect sizes for 5-meter sprint performance across post-training time points, with larger effects observed at 4–8 minutes. HJ-PT and CJ-PT exhibited small negative effects, with no significant PAPE effects detected. Furthermore, Pearson correlation analysis indicated no significant associations between sprint performance and the time to peak PAPE after any exercise (P > 0.05). Conclusion This study provides preliminary insights into the short-term effects of different plyometric-based conditioning activities (CAs) on short-distance sprint performance. Vertical jump plyometric training showed potential benefits, though findings are limited by small sample size and no control group. Horizontal and combined training did not produce significant PAPE effects, likely due to differences in time-to-peak and cumulative fatigue. Future studies should include a larger sample size, further investigate responses in both sexes, control for confounding factors, and use surface electromyography to clarify the interactions between CA types and recovery.